EXPLORING CONSUMERS’ RESPONSES TO ADVERTISING THAT CHALLENGES BEAUTY IDEALS THROUGH BRAND AMBASSADOR: ANALYSIS OF AUDIENCE RECEPTION TOWARD PANTENE INDONESIA’S BYE#RAMBUTCAPEK, HELLO #RAMBUTKERECHARGED YOUTUBE AD WITH CELEBRITY ENDORSER KEANU ANGELO - Sekar Dewi Pramana, Antonia Rachel; Surayya Ulfa, Nurist; Bayu Widagdo, Muhammad (Interaksi Online, 2024)
This research explores how Pantene Indonesia challenges the perception that beauty products are exclusively for women through its advertising campaigns, particularly by featuring male influencers like Keanu Angelo in its promotions for the Pantene Miracle Hair Supplement. As Indonesia's beauty industry, especially hair care, continues to grow, Pantene has sought to redefine its brand image in response to competitive pressures and traditional beauty standards. Utilizing Stuart Hall's Reception Theory, qualitative interviews with five informants reveal diverse audience responses shaped by their social backgrounds and personal experiences. Findings indicate a spectrum of interpretations, including dominant, negotiated, and oppositional positions, with some informants exhibiting a dual negotiated-oppositional stance that acknowledges the ad's inclusive message while critiquing conflicting elements. These insights highlight the complexity of audience engagement with media messages and suggest that while Pantene's strategy has the potential to shift perceptions and challenge stereotypes, it must also incorporate broader representations and community outreach efforts to resonate authentically with evolving societal beauty standards.